The Foot That Broke Both Hips: A Case Report and Literature Review of Tumor-Induced Osteomalacia. (14th September 2017) - Beygi, Sara; Denio, Alfred; Sharma, Tarun S.
Abstract : Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome characterized by hypophosphatemia and clinical symptoms of osteomalacia. Only discussed as case reports, there is still limited knowledge of this condition as a potentially curable cause of osteomalacia among clinicians and pathologists. In this article, we present a case of tumor-induced osteomalacia in a 59-year-old gentleman followed by an up-to-date review of the existing literature on TIO.